Correction: First principles study of electronic and optical properties and photocatalytic performance of GaN–SiS van der Waals heterostructure. Issue 17 (13th April 2023) - Sabir, S. S.; Farooq, M.; Din, H. U.; Alam, Q.; Idrees, M.; Bilal, M.; Amin, B.
Abstract : Correction for 'First principles study of electronic and optical properties and photocatalytic performance of GaN–SiS van der Waals heterostructure' by S. S. Sabir et al., RSC Adv., 2021, 11, 32996–33003, ; https://doi.org/10.1039/D1RA06011B .